Alcohol consumption patterns of the Hungarian general and Roma populations - Ali Abbas Mohammad Kurshed; Ali Abbas Mohammad Kurshed; Ali Abbas Mohammad Kurshed; Ferenc Vincze; Péter Pikó; Zsigmond Kósa; János Sándor; Róza Ádány; Róza Ádány; Judit Diószegi (Frontiers Media S.A., 2023)
IntroductionHarmful alcohol use is a significant public health problem worldwide, though the alcohol-related burden affects disproportionately certain populations and ethnic minorities, with the WHO European Region being the most heavily affected and putting an increased risk on Roma populations. This ethnic minority group is the largest and most vulnerable ethnic minority in Europe and Hungary as well.MethodsThe present study aims to describe and compare the alcohol consumption behaviors of the Hungarian general and Roma populations using the Alcohol Use Disorders Identification Test (AUDIT), which provides a comprehensive view of alcohol consumption behavior. In addition, a decomposition analysis was performed when the multivariate logistic or Poisson regression model showed significant differences between the two samples.ResultsOur findings suggest that Roma people in our study sample experience more alcohol-related harm, even when considering past problems. The decomposition analysis revealed that gender and relationship status differences act more intensely among Roma than non-Roma when considering alcohol-related harm.DiscussionEqualizing these differences would be expected to reduce the Hungarian general and Roma populations' alcohol-related harm frequency gap. Investigating alcohol-attributed harms at the ethnicity level provides important information to identify high-risk groups and, thus, to design and implement more targeted and accessible interventions for alcohol problems.